Comparison of Self-inferiority and Responsibility in Adopted Adolescents and their peers in Tehran - Sahar Bazrgar; Malek Mirhashemi (Shahid Beheshti University of Medical Sciences, 2018)
Background and Objective: Adoption is a social, psychological and legal phenomenon and its implications are of importance in the daily life of adopted children and their parents. The objective of this study was to identify the difference between self-inferiority and responsibility among adopted adolescents and their peers in Tehran. Materials and Methods: This causal-comparative study was in conducted in Tehran in 2016. Participants included adolescents who were adopted by Tehran Welfare Organization and their peers in two high schools in two municipality districts of Tehran Districts Three and Seven, in 2016. Adolescents who were adopted were selected by using convenience sampling method from health centers affiliated to Tehran Welfare Organization. Peers were selected by random sampling in two high schools in Districts Three and Seven. The questionnaire of responsibility (CPI-RE) and self-inferiority scale were used for data collection. Data were analyzed by multivariate analysis of variance and analyzed by SPSS.18 software. Results: As many as 95 adolescents in the study group and 105 in the control group participated in the study. The mean (SD) age of the study and control group was 15.7 (1.6) and 16.2 (1.9) respectively. There was no significant difference between the mean (SD) self-inferiority score of the study and control group: 2.1 (0.5) versus 2.1 (0.6), F=0.07, p>0.05). The mean (SD) responsibility score was significantly higher among the control group than the study group: 1.5 (0.7) versus 0.4 (0.1), F = 8.42, p <0.05. Conclusion: Study showed the level of responsibility of adolescents who were adopted was lower than that of their peers. However, there was no difference between their self-inferiority